Carok & The Media: Unravelling Narratives Of Traditional Violence In Madura On Kompas.Com And Detik.Com - Rahman, Fatlur; Ariyanto, Panji Putra (Institut Agama Islam Negeri Kendari, 2024)
This study analyzes the framing of the news of the carok action in Bangkalan Madura in the news period 12-15 January 2024 reported by Kompas.com and Detik.com. Carok, as a tradition of violence rooted in Madurese culture, is often highlighted by the media. This study uses a qualitative approach using Robert N. Entman's framing analysis theory, this study explores how the two media framed the incident, highlighting aspects that are selected and emphasized to influence readers' perceptions. And the results of the analysis show that Kompas.com and Detik.com gave different emphases in their narratives, focusing on the chronology of events, cultural roots, and social impact of the carok action. This research provides insight into how the media can shape social reality and influence public opinion regarding the tradition of violence in Madura.Keywords: Carok Madura, Framing, Media Reality.